Review On: Object Detection and Tracking To Implement Human- Machine Interaction (International Journal of Engineering and Computer Science, 2014)
In today’s era of technology, evolution has occurred in every possible field. Mankind is witnessing a virtual world of internet more often since the last decade. If today’s demand is transmutation from physical to virtual, so has the concept of virtual blackboard come up. Following the domain of computer vision the system makes use of an object to interact with the digital world. An object with some specifications is detected by the system through webcam, movements of the object are tracked and depending upon the color of the object, predefined functionalities are provided by the system. Main objective of developing the system is to provide all the functionalities of a physical blackboard and change the traditional approach altogether.